Case Report: Blood and cerebrospinal fluid mNGS-assisted diagnosis Toxoplasma gondii infection-associated with hemophagocytic syndrome and systemic lupus erythematosus - Chen, Xingyuan; Yu, Xuegao; Deng, Jiankai; Yang, Juhua; Chen, Peisong (Frontiers in Medicine, 2025)
BackgroundReactivation of latent Toxoplasma gondii (T. gondii) infection is more prevalent than primary infection in patients with autoimmune diseases. We present a rare case of systemic lupus erythematosus (SLE) and hemophagocytic syndrome (HPS) associated with T. gondii infection.Case presentationWe describe the case of a young girl with SLE and HPS who presented with fever, dyspnea, and pancytopenia. The patient's T. gondii infection was diagnosed through the detection of double-positive IgM and IgG antibodies. Metagenomic next-generation sequencing (mNGS) analysis of both plasma and cerebrospinal fluid (CSF) samples revealed a high concentration of T. gondii DNA. The patient demonstrated a positive response to a combined treatment regimen consisting of anti-Toxoplasma medications and glucocorticoids.ConclusionsCo-infection with uncommon pathogens is not uncommon in patients with autoimmune diseases. In individuals with immune disorders and positive T. gondii IgM antibodies, mNGS analysis of peripheral blood samples proves valuable in diagnosing disseminated T. gondii infection.